EFFECT OF FERMENTATION TIME AND ROASTING TEMPERATURE ON THE CHARACTERISTICS OF WINE COFFEE ARABICA SEMERU - Maligan, Jaya Mahar; Kosasih, Swandayani Utami; Nurcholis, Mochamad; Sriherfyna, Feronika Heppy (Department of Food Science and Biotechnology, Faculty of Agriculture Technology, Universitas Brawijaya, 2024)
This study was conducted to identify the best fermentation period and roasting temperature for semeru arabica wine coffee. This study used the factorial RSBD research approach (three levels of roasting temperature and four levels of fermentation duration). Physicochemical and organoleptic data were analyzed using ANOVA 5%, LSD 5%, and HSD 5%. Then, the best treatment's ash alkalinity, coffee juice content, and caffeine level were assessed. According to the study, the fermentation period has impact on the moisture level of green beans, the moisture and ash content of roasted beans, acidity, body, and balance. The water and ash content of roasted beans, aroma, flavor, acidity, aftertaste, body, balance, and overall attribute, are influenced by the roasting temperature. Then the interaction between factors significantly affects the water content of roasted beans, flavor, acidity, and body. The best treatment achieved a total score of 81.83 (40 days, 200 °C).